Family Social Support and Quality of Life for Diabetes Mellitus Patients at RSUP H. Adam Malik Medan 2024 - Pane, Jagentar; Martini, Sri; Lady Sheba Angelina Purba (Jurnal Midwifery, 2025)
Introduction Social support is a form of support given to family members who experience health problems including diabetes mellitus, which includes emotional support and appreciation, such as providing attention, affection and comfort. Quality of life refers to how a person views their life regarding their goals, hopes, and attention to the lives of those affected by the cultural values ​​of their environment. Diabetes mellitus (DM) is a type of disease that lasts a long time due to abnormalities in the insulin hormone and insulin function; so that the body experiences disturbances in the metabolism of carbohydrates, proteins and fats which results in an increase in blood glucose levels. The aim of this research is to find out what family social support is and the quality of life of diabetes mellitus patients at H. Adam Malik Hospital Medan 2024. Method This research uses a descriptive research design. The sampling method is purposive sampling with a total of 90 respondents from a population of 1388 patients. Result The results of this research showed that family social support for diabetes mellitus patients at H. Adam Malik General Hospital Medan 2024 is in the good majority with 43 patients (47.8%), while the quality of life for diabetes mellitus patients at H. Adam Malik Hospital Medan 2024 62 patients (68.9%) have moderate quality of life. Conclusion Even though the majority of results are moderate, it is recommended that hospitals in providing health services to diabetes mellitus patients not only provide health services but can involve families in accompanying patients.